Translocation of effectors: revisiting the injectosome model. (May 2011) - Sal-Man, Neta; Croxen, Matthew A; Finlay, B Brett
Evaluation of: Akopyan K, Edgren T, Wang-Edgren H et al. : Translocation of surface-localized effectors in type III secretion. Proc. Natl Acad. Sci. USA 108(4), 1639––1644 (2011). Type III secretion systems suppress host immune response and modify cell-signaling and regulation pathways by translocation of virulence proteins, called effectors, from the bacteria into the cytosol of the target cells. The common belief was that effectors translocate by a single step mechanism through a continuous channel built up by type III secretion systems. In this article, Akopyan et al. propose an alternative, and possibly parallel, two-step model to translocate effectors into target cells. According to their model, effectors first localized on the surface of the bacterial membrane, followed by a type III secretion system-dependent entry into the host cell.